The impact of proprioception impairment on gait function in stroke survivors: a comprehensive review - Kochman, Maciej; Kasprzak, Marta; Kielar, Aleksandra (Frontiers in Neurology, 2025)
Stroke survivors often experience sensory, cognitive, and motor consequences with gait disorders as a common problem. Therefore, there is a need for a deeper understanding of how neurological deficits affect the functioning of patients after a stroke. Current scientific literature lacks research on proprioception impairment, and gait recovery after stroke. In this narrative review, we discussed and summarized the current knowledge about the abnormal post-stroke gait pattern, the role of proprioception in motor control, methods of proprioception assessment, and the association between abnormal gait and proprioception deficit in stroke survivors. The present findings must be interpreted with some caution as current evidence is limited, as well as the correlation does not imply causation and might be underestimated by attributes of current tests for proprioception and motor function. Further studies are needed to better explain the mechanisms behind proprioception deficits and their association with functional recovery, as well as to investigate the cause-effect relationship.